Sistem Pemantauan Sawah Mobile Berbasis Internet of Things - Muhamad Maulana Syahaddan; Anita Fira Waluyo (STMIK Budi Darma, 2023)
The use of generation 4.0 technology in the Internet of Things (IoT) as a means of communication via the internet network by integrating with electronic devices to carry out activities Meanwhile, the majority based on the Central Bureau of Statistics for Population 15 Years and Over Working according to Main Job Fields in August 2022 in the Agriculture, Forestry, and Fisheries sectors is 38,703,996. The problem is that in 2021, the rice harvest was around 10.41 million, a decrease of 245.47 thousand compared to the harvest in 2020. This was due to several reasons, including rat pest attacks and less than optimal water use for rice, which caused the soil to become dry. From this problem, a mobile technology was created that was integrated with Arduino and ESP8266 devices based on the Internet of Things. The objectives of the rice field monitoring application include obtaining information on soil moisture, irrigation water level, pump water level, and automating pest repellents using speakers that emit frequency sounds. This application also makes it easier for farmers to monitor the condition of their rice fields remotely and at any time, reducing the fuel costs they have to incur every time they travel to the fields. This application is also very effective for people who have rice fields but are constrained by their main job. The advantage of making an application lies in the use of a database, namely the Firebase database, because storing information about soil moisture, irrigation water levels, and pest expulsion is quickly conveyed and updated in real time by sending data from Internet of Things tools to mobile applications.